Epigenetic targeting of bromodomain protein BRD4 counteracts cancer cachexia and prolongs survival - Marco Segatto (Nature Portfolio, 2017)
Cachexia is a metabolic syndrome leading to muscle and adipose tissue loss in majority of cancer patients. Here the authors show that, in a mouse model, BET inhibitor JQ1 counteracts muscle and adipose tissue wasting tempering cachexia and prolonging survival through a mechanism unrelated to tumour growth.